Trust and control at the workplace: evidence from representative samples of employees in Europe - Christian Grund; Christine Harbring (Institute for the Study of Labor (IZA), 2009)
Based on two representative samples of employees, the German Socio Economic Panel and the European Social Survey, we explore the relation between certain measures of control in employment relationships (i.e. working time regulations, use of performance appraisal systems, monitoring by supervisors, autonomy to organize the work) and individuals' inclination to trust others. Trust is measured by the general trust question like in most other economic studies based on surveys. We find that strict working time regulations, monitoring and lack of autonomy - all indicators for control at the workplace - are negatively related to trust. Moreover, we contribute to the literature on trust by gathering hints to other potential determinants of trust.
urn:nbn:de:101:1-2009082505
Keywords: D03; J81; M12; M5; 330; autonomy; control; monitoring; performance appraisal; regulation of working time; trust; Arbeitsbeziehungen; Leistungskontrolle; Vertrauen; Betriebsklima; Personalbeurteilung; Deutschland; EU-Staaten